Sosialisasi Pengenalan Kejahatan Siber Phishing dan Scam di Kelurahan Bandarharjo Kota Semarang - Siti Noor Chotimah; Silvia Nurvita; Ratih Kumala Dewi; Vinny Natalia Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Increasingly advanced technological developments can also have negative impacts. One of them is cybercrime, namely phishing. The existence of phishing will also refer to a scam or fraud. This research aims to increase public knowledge in the Bandarharjo village environment about the dangers of phishing and scams in daily life. This community service activity is an effort to increase community knowledge. The method of transmitting the material is through giving lectures, discussions, and distributing leaflets. The use of these methods and media is effectively applied to increase public awareness regarding the dangers of phishing and scams. According to the evaluation carried out, the level of public knowledge has improved and they are aware of the importance of socialization regarding phishing-type cybercrimes. It is hoped that this activity can have a positive impact and long-term benefits in raising awareness of the dangers of cybercrime in the future in people's daily lives